Disturbance decoupled fault reconstruction using sliding mode observers - Kok, Yew Ng; Chee, Pin Tan; Akmeliawati, Rini; Edwards, Christopher (2008)
The objective of a robust fault reconstruction scheme is to generate an accurate reconstruction of the fault that is unaffected by disturbances. A typical method for robust fault reconstruction is to reconstruct the faults and disturbances, which is conservative and requires stringent conditions. This paper investigates and presents conditions that guarantee a fault reconstruction that rejects the effects of disturbances, which are less stringent than those of previous work. A VTOL aircraft model is used to validate the work of this paper.